Mainstream Media Politics in the Presidential Election of the Republic of Indonesia 2019 - Anang Sujoko (International Journal of Science and Society, 2019)
Mass media has the power to build a discourse on public discussion. This strength should be used in carrying out its function as a watchdog in democratic practice. The mass media must break away in a position as part of the executive or legislative because he himself is the fourth force in the pillar of democracy. In the 2019 Indonesian Presidential Election (Pilpres) the mass media showed practices that weakened this position with the presence of affiliated media owners or even became part of the political parties supporting one of the candidate pairs in the 2019 Presidential Election. This paper is critical thinking about how politics mainstream mass media in Indonesia in polarizing support to candidate pairs. The data are collected through observation of media content and in-depth interviews with informants from media workers and informants who have competence in the field of mass media. The results of the study show that mainstream mass media tends to still be positioned as the main source of information in the five-year democracy event. The preaching of mainstream mass media still shows partiality to certain candidate pairs by not expressing criticism and vice versa often showing criticism on other candidate pairs. The mass media that have affiliations to political parties tend to show partiality to the authorities and ignore the critical role in overseeing government practices. The oligarchy of the media industry in Indonesia has not shown the role of overseeing the social and political environment.